2020
DOI: 10.1158/1078-0432.ccr-20-2682
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and Genome-Wide Analysis of Multiple Severe Cisplatin-Induced Neurotoxicities in Adult-Onset Cancer Survivors

Abstract: Purpose: Cisplatin is a first-line chemotherapeutic for many cancers, but causes neurotoxicity including hearing loss, tinnitus, and peripheral sensory neuropathy. However, no study has comprehensively characterized risk factors for developing multiple (>1) severe neurotoxicities.Experimental Design: The relationship between multiple severe neurotoxicities and age, cumulative cisplatin dose, medical history, and lifestyle/behavioral factors was evaluated in 300 cisplatintreated testicular cancer survivors usin… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 40 publications
1
4
0
Order By: Relevance
“…Continued smoking in patients with cancer is associated with significant incremental costs for further cancer treatment when first‐line therapy fails 44 . In addition, previous investigations also demonstrated significant increases in the neurotoxic effects of chemotherapy in smokers, supporting the findings of the current study 12,45 . The 2020 Surgeon General's Report 46 indicates that smoking cessation improves patients' quality of life and adds up to 10 years to their lifespan.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Continued smoking in patients with cancer is associated with significant incremental costs for further cancer treatment when first‐line therapy fails 44 . In addition, previous investigations also demonstrated significant increases in the neurotoxic effects of chemotherapy in smokers, supporting the findings of the current study 12,45 . The 2020 Surgeon General's Report 46 indicates that smoking cessation improves patients' quality of life and adds up to 10 years to their lifespan.…”
Section: Discussionsupporting
confidence: 79%
“…44 In addition, previous investigations also demonstrated significant increases in the neurotoxic effects of chemotherapy in smokers, supporting the findings of the current study. 12,45 The 2020 Surgeon General's Report 46 indicates that smoking cessation improves patients' quality of life and adds up to 10 years to their lifespan. In addition, with clear evidence that smoking cessation is beneficial both before and after cancer treatment for many cancer types, this report 46 Cisplatin-based therapy consists primarily of either three cycles of BEP or four cycles of EP resulting in a cumulative dose of 300 or 400 mg/m 2 cisplatin, respectively although occasional patients may receive doses of cisplatin greater than 400 mg/m 2 .…”
Section: Other Findingsmentioning
confidence: 99%
“…RGS17 was reported as a negative modulator of G-protein-coupled receptor signals in several cancers, 33 and the variants of RGS17 were recently reported to be associated with cisplatin-induced neurotoxicities via a gene-based analysis of the results of a GWAS. 34 It was interesting to find that the genetic variants of RGS17 are associated with drug-induced adverse events, but there is no report about the role of RGS17 in IBD or mesalamine pharmacokinetics. Moreover, we discovered that an SNP exists very close to RP11-306O13.1, which is a long intergenic noncoding RNA.…”
Section: Discussionmentioning
confidence: 99%
“…This result has been recognized by peers ( 61 , 62 ). It was also found that increased FAM20C expression is related to decreased cisplatin sensitivity in testicular cancer ( 63 ).…”
Section: The Role Of the Secretory Pathway Kinases Or Kinase-like Pro...mentioning
confidence: 98%